Мова фольклорних пісенних пам’яток у науково-дослідних студіях Світлани Яківни Єрмоленко - Беценко, Т. П.; Беценко, Тетяна Петрівна; Betsenko, Т. Р. (ВД "Гельветика", 2017)
У статті розглянуто науковий доробок С.Я. Єрмоленко, присвячений висвітленню проблем мови фольклорно-пісенних пам’яток. Схарактеризовано досягнення вченого в означеній галузі наукових знань. Осмислено внесок дослідника в розбудову вітчизняних лінгвофольклористичних студій.

The scientific potential of S. Ya. Ermolenko, devoted to the illumination of the problems of the language of folklore and song monuments, is considered in the article. The achievements of the scientist in this field of scientific knowledge are characterized. The researcher s contribution to the development of national linguistic and folklore studios is meaningful.
Беценко Т. П. Мова фольклорних пісенних пам’яток у науково-дослідних студіях Світлани Яківни Єрмоленко / Т. П. Беценко // Одеський лінгвістичний вісник. – 2017. – Вип. 10. – Т. 2. – С. 12-15.
Keywords: Research Subject Categories::HUMANITIES and RELIGION; фольклор; мова фольклору; фольклорний стиль; школа лінгвофольклористики; природа фольклорного слова; folklore; language of folklore; folklore style; school of linguo-folklore; nature of thefolklore word